Freestyle race patterns in Paralympic swimmers with varying impairments - Daly, D.; Schega, L.; Satkunskiene, D.; Vanlandewijck, Y. (First international symposium sciences and practices in swimming, 2006)
The purpose here was to examine certain race segment times and stroking variables in two groups of Paralympic swimmers matched by functional class and race performance. Start time, Turn time, Finish time and mid-pool swimming speed and SR and SL were measured in two groups (Cerebral Palsy(CP) and Limb Loss (Amp)) of Paralympic 50-m, 100-m and 400-m freestyle finalists matched by gender, class and race performance. Groups showed identical race speed patterns at all 3 distances. In the two shorter races CP swimmers had significantly longer stroke length (>14%) at the same swimming speed. Swimmers with diverse impairments achieve the same race result by adjusting stroking variables. This Supports the use of functional classification in swimming in which diverse impairment groups compete in the same classes.